2022
DOI: 10.3389/fmars.2022.804648
|View full text |Cite
|
Sign up to set email alerts
|

New Insight Into the Reproductive Biology and Catch of Juveniles of the Lutjanus purpureus in a Portion of the Great Amazon Reef System Off the Northern Brazilian Coast

Abstract: The Southern red snapper, Lutjanus purpureus, is a valuable economic resource, especially in international market. However, no recent data are available on the reproductive biology of this species in Brazilian waters, in particular, the stock found on the Amazon reef. The present study evaluated the population structure and reproductive biology of L. purpureus, and the volume of the catch of juveniles taken by the local commercial fisheries. A total of 923 specimens were analyzed, of which, 577 were female and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…However, since the early 1990s, studies aimed at understanding the bioecological aspects of Red Snapper have been carried out, seeking information that could elucidate a targeted and efficient management (Costa et al, 2017;Freire et al, 2022;Souza et al, 2003Souza et al, , 2006Souza et al, , 2008. In this context, parallel to these initiatives, no studies were found in the literature that use remote sensing oceanographic data in the investigation of Red Snapper catches in Amazon coast.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, since the early 1990s, studies aimed at understanding the bioecological aspects of Red Snapper have been carried out, seeking information that could elucidate a targeted and efficient management (Costa et al, 2017;Freire et al, 2022;Souza et al, 2003Souza et al, , 2006Souza et al, , 2008. In this context, parallel to these initiatives, no studies were found in the literature that use remote sensing oceanographic data in the investigation of Red Snapper catches in Amazon coast.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recognizing the exogenous effects of the environment and associating them with fishing intensity is necessary since the depletion of Red Snapper stocks seems evident given the structuring of fishing (Freire et al, 2022;Freire & Pesca, 2019;Mescouto, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catches were not monitored when landed, and fishery statistics have not been collected since 2007 (Isaac et al, 2009). This overall lack of minimum quantity of data on which to base catch projections was not unique to the C. acoupa fishery but is common to most artisanal and industrial fisheries of the northern Brazilian coast (Araújo et al, 2022; Freire et al, 2022).…”
Section: Discussionmentioning
confidence: 99%